Emergence of blood clotting disorders resulting from COVID vaccines inoculations - Eichinger, Sabine (Henry Stewart Talks, 2021)
The frequency of clotting side-effects in COVID-19 vaccines, The characteristics of these side-effects and how they compare to other clotting disorders, What is known regarding the mechanisms underlying these side effects, What is known regarding populations at greater risk of suffering these side effects